Dialog Antar Agama sebagai Implementasi Pendidikan Perdamaian - Nur Ashilla, Fathya; Tari, Natia; Rizki Akbar, Muhammad (Integritas Terbuka: Peace and Interfaith Studies, 2024)
Interfaith dialog plays an important role in promoting peace and understanding in diverse societies. This study examines the implementation of interfaith dialog as a key component of peace education. Using a comprehensive literature review approach, this study explores the role of interfaith dialog in the implementation of peace education. The Halaqah Damai program emerged as a concrete step to nurture tolerance, break down stigma, and foster a harmonious and inclusive society. By encouraging and utilizing dialogue as a connecting tool among individuals of different religions, peace education initiatives aim to foster mutual understanding and cooperation among Indonesia's diverse population.